Evaluation of Anticoccidial Activity of Citrus aurantium L. Ethanolic Leaf Extract against Experimental Eimeria tenella Infection in Broiler Chickens (Gallus gallus domesticus) - Abubakar Nuhu Ishaq; Dahiru Sani; Shuaibu Akpai Abdullahi; Kelvin Olutimilehin Jolayemi; Abdullahi Aliyu Ebbo; Isa Danladi Jatau; Ibrahim M.K. Gadzama (Elsevier, 2022)
Background: Coccidiosis is a debilitating poultry disease that costs the world more than £10.4 billion annually. Citrus aurantium L, also known as bitter orange, belongs to the family Rutaceae, it's been used in traditional Chinese medicine to treat nausea, constipation, cancer, cardiovascular effect, and as antioxidant. Anticoccidial activity of the ethanolic leaf extract of Citrus aurantium L. against experimental Eimeria tenella infection was studied in broiler chickens. Methodology: C. aurantium leaves were collected, authenticated, pulverized and extracted using ethanol. Thirty-six broiler chicks were obtained and thirty chickens were experimentally infected with 20,000 sporulated Eimeria tenella oocysts and assigned randomly into six groups of six chickens each. Group A was uninfected and untreated (negative control), group B served as infected-untreated control, group C were infected and treated with a standard drug; amprolium 1g/L of drinking water (positive control), groups D, E, and F were infected and treated with ethanolic leaf extract of C. aurantium at 125, 250 and 500 mg/kg orally, respectively, for seven consecutive days. Weight gain was calculated and the oocysts per gram of faeces were counted using the McMaster counting apparatus. Blood samples from each experimental group were collected on days 7 and 14 post-infection for haematological examination. Results: Results revealed that treatment with ethanolic leaf extract of C. aurantium dose-dependently decreased the E. tenella oocysts shedding, increase body weight, improved caecal lesion and significantly (p < 0.05) increased the PCV, TRBC and Hb concentration with significantly decreased (p < 0.05) TWBC of the infected chickens. Conclusion: C. aurantium provided beneficial effects against E. tenella-induced coccidiosis in broiler chickens. The plant should be further validated to investigate the essential compounds responsible for the anticoccidial effect.